Beispiel Nr: 18
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +1 y =1\\ 2 x +2 y = 2 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 1 x +1 y =1\\ II \qquad 2 x +2 y = 2 \\ \text{I nach y auflösen}\\ 1 x +1 y =1 \\ 1 x +1 y =1 \qquad /-1 x\\ 1 y =1 -1 x \qquad /:1 \\ y =1 -1 x \\ \text{II nach y auflösen}\\ 2 x +2 y =2 \\ 2 x +2 y =2 \qquad /-2 x\\ 2 y =2 -2 x \qquad /:2 \\ y =1 -1 x \\ \text{I = II}\\ 1 -1 x =1 -1 x \qquad /+1 x /-1 \\ 1-1 =-1 x +1 x \\ \\ L= unendlich\end{array} & \begin{array}{l} I \qquad 1 x +1 y =1\\ II \qquad 2 x +2 y = 2 \\ \text{I nach x auflösen}\\ 1 x +1 y =1 \\ 1 x +1 y =1 \qquad /-1 y\\ 1 x =1 -1 y \qquad /:1 \\ x =1 -1 y \\ \text{II nach x auflösen}\\ 2 x +2 y =2 \\ 2 x +2 y =2 \qquad /-2 y\\ 2 x =2 -2 y \qquad /:2 \\ x =1 -1 y \\ \text{I = II}\\ 1 -1 y =1 -1 y \qquad /+1 y /-1 \\ 1-1 =-1 y +1 y \\ \\ L= unendlich\end{array} \end{array} $